Enhancing spiritual inclusion: A systematic literature review on the intersection of disabilities and worship practices among people with disabilities - Mohd Zahir Abdul Rahman; Shah Rizul Izyan Zulkiply; Noornajihan Jaafar; Siti Fatimah Mohd Tawil; Nurul Asiah Fasehah Muhamad; Dg. Hafizah Ag. Basir (Universal Publishers, 2024)
Purpose: This article aims to conduct a comprehensive systematic literature review (SLR) of previous research focused on PWD and worship, with a specific emphasis on understanding, needs, social support and challenges. Design/methodology/approach: The study adopts the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines to structure the SLR, drawing on this widely used publication standard within the fields of medicine and public health. Prism’s 27-item framework aids in the formulation of precise research questions and facilitates systematic searching and synthesis of studies, thereby minimizing biases. Findings: This study identifies four main themes: understanding, needs, social support and challenges. Research limitations/implications: To find articles and related resources included in this SLR, three main databases, Scopus, and two supporting databases, BASE and Google Scholar, were used. Practical implications: As a result, the theme of the challenge is the aggravation that, if not solved, has a detrimental influence on the disabled, particularly in terms of awareness and financial aid. If referred to, the findings of this study are expected to aid relevant parties in developing policies that are in keeping with the capabilities and requirements of the disabled in assisting them in performing worship more successfully. Originality/value: This article will have a significant impact on researchers, the PWD community, non-governmental organizations (NGOs), and governing bodies.